SUPPRESSION OF MANGANESE SUPEROXIDE DISMUTASE ACTIVITY IN ROTENONE-TREATED HUMAN GLIOBLASTOMA T98G CELLS REDUCES CELL VIABILITY - Wanandi, Septelia Inawati; Hardiany, Novi Silvia; Siregar, Nurjati Chairani; Sadikin, Mohamad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: Glioma is the most common human primary brain tumor which is highly resistant to oxidative stress-based anticancer. The aim of this study was to analyze the effect of rotenone-induced reactive oxygen species (ROS) on the modulation of manganese superoxide dismutase (MnSOD) expression and cell viability in human glioblastoma (GBM) T98G cells. Methods: In this in vitro experimental study, T98G cells were treated with high-dose rotenone (0.5, 5, and 50 Î¼M, respectively). Following rotenone treatment and intracellular ROS, both peroxide and superoxide radicals were determined. Moreover, we analyzed MnSOD mRNA expression, protein, and specific activity, as well as cell survival including viability, proliferation, apoptosis, and mitochondrial structure. Results: High-dose rotenone treatment of T98G cells significantly increased intracellular ROS and MnSOD mRNA, but its protein and specific activity definitely decreased. The treatment also led to a reduction of cell viability, enhancement of apoptosis, and disruption of mitochondrial integrity. Conclusion: Overproduction of ROS in rotenone-treated human GBM T98G cells could suppress the MnSOD protein level and activity even though mRNA synthesis has been increased. This modulation led to reduced survival of T98G cells through induction of cell death rather than inhibition of cell proliferation.